Pendampingan Teknis Pemeriksaan Fisik Kuantitas Item Pekerjaan pada Pembangunan Gedung - Dewi, Norminawati; Marlia Adriana; Ines Saraswati Machfiroh; Tekad (Jurnal Masyarakat Indonesia (Jumas), 2025)
Physical inspections of construction are the result of follow-up activities from document analysis conducted by the relevant parties, where weaknesses in the reporting of audit results or physical inspections of construction are identified. The physical inspection of construction also seeks significant issues due to differences in interpretation regarding the calculation of work volume during the tender process and the evaluation of work progress. Community Service Activities (PKM) are one of the Tri Dharma of Higher Education, alongside education, teaching, and research. Through this activity, it is hoped that the target community can obtain useful information and then apply and further develop the information provided by the speakers. The implementation method is carried out in two ways: desk audits and direct field inspections. Preliminary surveys/desk audits are conducted on the packages being examined, in accordance with the Work Order, aimed at detecting potential early deviations in the implementation of the packages to be examined. The results of the community service indicate the need for learning development activities through collaborative or community service initiatives aimed at providing assistance in line with the area of expertise. The results of this service also provide recommendations and analyses from experts that are useful for maintaining orderly public financial administration in its usage, thereby allowing for the anticipation of irresponsible parties. The assistance in community service activities also imparts specific knowledge to students regarding the direct application of scientific knowledge. The objective of the construction inspection is to ensure the orderly execution and results of construction work, covering physical aspects including volume and quantity of construction, planning, procurement, management of implementation, and contract control in building construction projects. Therefore, the implementation of PKM provides a supportive solution in the physical inspection of items related to building construction.